Influence of different layout of rigid and flexible structures on methane explosion in oil and gas gathering and transportation station - Weifeng Duan; Shitong Liu; Kan Du; Yulong Duan; Huaixu Liu (PLoS ONE, 2026)
Oil and gas gathering and transportation station is the core hub of oil and gas production, processing and transportation. Its safe operation is directly related to the stability of energy supply and the safety of personnel and property. To solve the problems of high explosion risk, limited overpressure attenuation and facilities vulnerable to explosion impact damage caused by rigid facilities in the oil and gas gathering and transportation station, based on the small-scale explosion experimental platform, this paper studies the space protection technology of flexible facilities, and discusses the gas explosion-proof effect of different sizes of flexible facilities in front of rigid facilities. The experimental results show that in most cases, the flame front velocity and flame explosion overpressure are positively correlated with the blockage rate of the flexible structure; When the blockage rate of flexible structure is less than or equal to the blockage rate of rigid structure, the flame velocity and explosion overpressure decrease with the decrease of the spacing, and the explosion protection effect is better; When the blockage rate of flexible structure is greater than the blockage rate of rigid structure, the smaller spacing may aggravate the explosion. The research results help to clarify the influence mechanism of flexible protective facilities on natural gas explosion pressure and flame characteristics, reveal the protection mechanism of flexible protective facilities on rigid facilities, and provide theoretical basis and scientific guidance for the protection layout design of rigid facilities and natural gas explosion protection technology in oil and gas gathering and transportation station.